2014
DOI: 10.1111/jphp.12232
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro/in-vivo characterization of trans-resveratrol-loaded nanoparticulate drug delivery system for oral administration

Abstract: The results, therefore, insight into the role of solubility enhancement and trounce enterohepatic recirculation for improving the oral bioavailability of t-RVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…176 Their research group also studied sustained release of trans-resveratrol in vitro and found higher solubility and dissolubility of trans-resveratrol. 68,175,176 In addition, a combination of one or two nanosized bioactive compounds has multiple health beneficial effects for certain diseases, which further reduces the multiple drug load. Curcumin and resveratrol encapsulated nanoliposomes have an antitumor effect against prostate cancer.…”
Section: Nanoresveratrolmentioning
confidence: 99%
See 4 more Smart Citations
“…176 Their research group also studied sustained release of trans-resveratrol in vitro and found higher solubility and dissolubility of trans-resveratrol. 68,175,176 In addition, a combination of one or two nanosized bioactive compounds has multiple health beneficial effects for certain diseases, which further reduces the multiple drug load. Curcumin and resveratrol encapsulated nanoliposomes have an antitumor effect against prostate cancer.…”
Section: Nanoresveratrolmentioning
confidence: 99%
“…Nanoencapsulation protects trans-resveratrol from this rapid conversion and enhances its bioavailability in systematic circulation for prolonged activity. 68,175 PLGA-coated resveratrol nanoparticles enhance the bioavailability of resveratrol for up to 4 days in a rat model. 176 Their research group also studied sustained release of trans-resveratrol in vitro and found higher solubility and dissolubility of trans-resveratrol.…”
Section: Nanoresveratrolmentioning
confidence: 99%
See 3 more Smart Citations